Hubungan Antara Kepuasan Karyawan, Produktivitas Kerja, Dan Kualitas Proses Produksi Terhadap Efisiensi Operasional PT. Kohler Manufakturing Indonesia - Armando, Rizki (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The purpose of this research is to study how employee satisfaction, work productivity, and production process quality affect the operational efficiency of PT Kohler Manufacturing Indonesia. In the competitive manufacturing industry, operational efficiency is a key measure of the success of a business. Factors such as job satisfaction affect employee morale and loyalty, and productivity demonstrates the ability of the workforce to achieve targets. Conversely, the quality of the production process contributes directly to the optimal use of resources and the minimization of product defects. Descriptive methods were used in this study; in addition, this study analyzed various internal and external factors of the company through SWOT analysis. The results show that the three factors are interconnected and contribute significantly to operational efficiency. Therefore, organizations should pay balanced attention to human resource, technical, and management elements to achieve sustainable and optimal operational performance.